A semiconducting iron-chelating nano-immunomodulator for specific and sensitized sono-metallo-immunotherapy of cancer - He, Shasha (2023)
Sono-immunotherapy holds great potential for deep tumor inhibition; however, smart sono-therapeutic agents to simultaneously eliminate 'domestic' tumor cells and regulate the 'community' tumor immune microenvironment have rarely been developed. Herein, we report a spatiotemporally controllable semiconducting iron-chelated nano-metallomodulator (SINM) for hypersensitive sono-metallo-immunotherapy of cancer. SINM consists of a semiconducting polymer (SP) backbone chelating iron ions (Fe3+ ) with thiophene-based Schiff base structure, and a hydrophilic side chain. Upon accumulation in tumors after systemic administration, SINM specifically arouses ferroptosis and M1 macrophage polarization due to its response toward the tumor redox environment; meanwhile, the chelation of Fe3+ enhances the sono-sensitizing effect of SPs, leading to enhanced generation of reactive oxygen species for immunogenic cell death. Such combined sonodynamic metallo-immunotherapy of SINM efficiently ablates deep tumor and spatiotemporally regulates immunophenotypes.